Career learning and career learning environment in Dutch higher education. (19th August 2014) - Meijers, Frans; Kuijpers, Marinka; Blessinger, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This article focuses on the effects of career development and guidance among students (age 17-23) enrolled in higher education in The Netherlands. First we explore whether the development of career competencies contribute to career identity, learning motivation, certainty of career choice and drop out, and also whether the learning environment affects these variables. In the study, four career competencies are identified: career reflection (reflective behaviour), work exploration (exploring behaviour), career action (pro-active behaviour) and networking (interactive behaviour). Aspects of the learning environment that are taken into account are practice- and inquiry-based curriculum and career guidance conversations. Design/methodology/approach A questionnaire-based study was carried out among 4820 students and 371 (school) career counsellors in 11 universities. Findings The results show that career competencies are related to learning motivation, career identity, certainty of career choice and drop out threat. The learning environment also contributes to these outcome variables. Students who participate in a practice-based and inquiry-based curriculum, and who have helping conversations about their study with their teachers, feel more motivated for learning, are more certain of their career choice and are less likely to quit their study. Research limitations/implications A limitation of this study is that, due to the cross sectional design with no control group, no strong evidence for effectiveness can be presented. Moreover, the lack of well validated instruments limits the value of the results. The explained variance of the outcome variables, however, does indicate that there are relationships between career competencies and career learning environment on one hand, and career identity, learning motivation and certainty of choices on the other. Practical implications Constructing and attributing meaning when engaging in these dialogues is of central importance; the development of personality traits and qualities only takes place when those learning find the content meaningful (and that is something quite different than content being considered 'necessary'. In order to achieve such a learning environment within the dominant educational culture, transformative leadership is essential. Such leadership, however, is rare in Dutch universities of applied sciences until now. Originality/value A limitation found in the research, as well as in actual career interventions in schools, is that they focus on change in students' knowledge, attitudes and decision-making skills, while students' behaviors are not examined. Hughes and Karp (2004) maintain that research should focus on exploring the relationships between guidance interventions and positive students' behavioral outcomes. Therefore, we concentrate – in search of the influence of school-based career interventions - not on decision-making skills, attitudes or knowledge but on actual career behavior, i.e. career competencies of students.